Composition for polishing

A polishing composition with specific silanol group density, inorganic salt, and oxidizing agent, and a pH of 6.0 or higher, effectively enhances the polishing speed and selectivity of silicon germanium, addressing the need for high-speed polishing with material selectivity.

JP7663331B2Active Publication Date: 2025-04-16FUJIMI INCORPORATED
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2020158993
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-09-23
Publication Date
2025-04-16
Estimated Expiration
2040-09-23

AI Technical Summary

Technical Problem

There is a need for a polishing composition that can achieve a high polishing rate for silicon germanium while maintaining sufficient selectivity over other materials like silicon nitride and silicon oxide.

Method used

A polishing composition is developed with abrasive grains having a silanol group density of 0 to 2.0 pieces/nm², an inorganic salt, and an oxidizing agent, with a pH of 6.0 or higher, to enhance the polishing speed and selectivity of silicon germanium.

Benefits of technology

The composition achieves a significantly increased polishing speed for silicon germanium and improved selectivity over other materials, such as silicon nitride and silicon oxide, thereby addressing the emerging demands for high-speed polishing with material selectivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007663331000001
    Figure 0007663331000001
  • Figure 0007663331000002
    Figure 0007663331000002
  • Figure 0007663331000003
    Figure 0007663331000003
Patent Text Reader

Abstract

To provide a polishing composition in which a polishing speed of silicon germanium is sufficiently high and a selection ratio of the polishing speed of silicon germanium is sufficiently high.SOLUTION: A polishing composition includes: abrasive grains; an inorganic salt; and an oxidizing agent, in which the number of silanol groups per unit surface area of the abrasive grains is more than 0 / nm2 and 2.0 / nm2 or less, and a pH of the polishing composition is 6.0 or more.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polishing composition. [Background technology]

[0002] As one of the technologies to reduce the power consumption and improve the performance (operation characteristics) of transistors, a channel using a high-mobility material (hereinafter, simply referred to as "high-mobility material") with a higher carrier mobility than Si is being investigated. In a channel made of such a high-mobility material and with improved carrier transport characteristics, the drain current that flows when a specified gate voltage is applied can be increased. This has the advantage that the power supply voltage can be reduced while a sufficiently high drain current is obtained. This advantage leads to higher performance of MOSFETs (metal oxide semiconductor field-effect transistors) at low power.

[0003] As high-mobility materials, III-V compounds, IV compounds, Ge (germanium), graphene made only of C (carbon), etc. are expected to be used. In particular, III-V compounds containing As and IV compounds containing Ge are being actively investigated.

[0004] The channel using the high mobility material can be formed by polishing an object to be polished such as silicon germanium (SiGe) having a portion containing a high mobility material (hereinafter also referred to as a high mobility material portion) and a portion containing a silicon material (hereinafter also referred to as a silicon material portion). For example, Patent Document 1 discloses a polishing composition used for polishing a substrate containing germanium. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Special Publication No. 2018-506176 Summary of the Invention [Problem to be solved by the invention]

[0006] Recently, silicon germanium, silicon nitride (SiN), and silicon oxide (SiO 2 In recent years, substrates containing silicon germanium and other materials such as silicon germanium have come to be used. For such substrates, there is a new demand for selectively polishing silicon germanium with respect to other materials while polishing silicon germanium at a high polishing rate. No consideration has been given to such demand in the past.

[0007] Therefore, an object of the present invention is to provide a polishing composition which has a sufficiently high polishing rate for silicon germanium and a sufficiently high selectivity for the polishing rate for silicon germanium. [Means for solving the problem]

[0008] In order to solve the above-mentioned new problem, the present inventors have conducted extensive research. As a result, the present inventors have discovered a method for producing a polishing agent comprising: an abrasive grain; an inorganic salt; and an oxidizing agent, the abrasive grain having a silanol group count of 0 / nm2 or less per unit surface area. 2 Exceeds 2.0 pcs / nm 2 It has been found that the above problems can be solved by a polishing composition having a pH of 6.0 or more and a viscosity of 100:1 or less, and has led to the completion of the present invention. Effect of the Invention

[0009] According to the present invention, it is possible to provide a polishing composition which has a sufficiently high polishing rate for silicon germanium and a sufficiently high selectivity for the polishing rate for silicon germanium. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] One embodiment of the present invention is a method for producing a polishing powder comprising the steps of: 2 Exceeds 2.0 pcs / nm 2The polishing composition of this embodiment has a sufficiently high polishing rate for silicon germanium, and is also excellent in polishing other materials (e.g., silicon nitride (SiN), silicon oxide (SiO 2 The selectivity of the polishing rate of silicon germanium to the polishing rate of the silicon germanium oxide can be sufficiently high.

[0011] The mechanism by which the above-mentioned effects of the present invention are obtained is believed to be as follows: However, the following mechanism is merely speculation, and the scope of the present invention is not limited thereto.

[0012] The number of silanol groups per unit surface area of ​​the abrasive grain is 0 / nm 2 Exceeds 2.0 pcs / nm 2 The hydrophobicity of the abrasive grain surface is increased by the above-mentioned condition, which is considered to result in an improvement in the polishing speed of silicon germanium oxidized by the action of the oxidizing agent.

[0013] In addition, the low number of silanol groups per unit surface area of ​​the abrasive grains reduces the amount of bound water present between the abrasive grains and the surface of the silicon germanium film, which is believed to facilitate contact of the abrasive grains with the silicon germanium film and improve the polishing rate of the silicon germanium.

[0014] Furthermore, the inclusion of inorganic salt in the polishing composition increases the electrical conductivity of the polishing composition, which is believed to result in the compression of the electric double layer formed on the surface of the silicon germanium film, improving the action of the abrasive grains and increasing the polishing rate of the silicon germanium film.

[0015] An embodiment according to one aspect of the present invention will be described below, but the present invention is not limited to the following embodiment.

[0016] In this specification, the range "X to Y" means "X or more and Y or less." Furthermore, unless otherwise specified, the operations and measurements of physical properties are performed under conditions of room temperature (20 to 25°C) and relative humidity of 40 to 50% RH.

[0017] [Polishing composition] (Abrasive grain) The polishing composition of this embodiment has a silanol group count of 0 / nm 2 Exceeds 2.0 pcs / nm 2 The abrasive grains include the following abrasive grains: The abrasive grains have the function of mechanically polishing an object to be polished, and increase the polishing rate of the object to be polished by the polishing composition.

[0018] The abrasive grains according to the present embodiment have a silanol group count per unit surface area of ​​the abrasive grains (also referred to simply as "silanol group density" in this specification) of 0 / nm 2 Exceeds 2.0 pcs / nm 2 There is no particular limitation as long as the silanol group density of the abrasive grains is within this range. If the silanol group density of the abrasive grains is within this range, the polishing rate of silicon germanium can be sufficiently increased. The silanol group density of the abrasive grains is preferably 0.5 particles / nm 2 More than 2.0 pieces / nm 2 More preferably, it is 1.0 particles / nm 2 More than 2.0 pieces / nm 2 The following is the result.

[0019] The number of silanol groups per unit surface area of ​​the abrasive grain can be calculated by the Sears method using neutralization titration described by GW Sears in Analytical Chemistry, vol. 28, No. 12, 1956, 1982-1983. The number of silanol groups is calculated by the following formula.

[0020]

number

[0021] The number of silanol groups per unit surface area of ​​the abrasive grains can be controlled by selecting the manufacturing method of the abrasive grains, etc.

[0022] The abrasive preferably comprises silica, more preferably comprises fumed silica or colloidal silica, and even more preferably comprises colloidal silica.

[0023] The shape of the abrasive grains is not particularly limited, and may be spherical or non-spherical. Specific examples of non-spherical shapes include polygonal prisms such as triangular prisms and square prisms, cylinders, bales in which the center of a cylinder is bulged out more than the ends, donut shapes in which the center of a disk is penetrated, plates, so-called cocoon shapes with a constriction in the center, so-called association-type spheres in which multiple particles are integrated, so-called confetti shapes with multiple protrusions on the surface, and rugby ball shapes, and various other shapes are not particularly limited.

[0024] When colloidal silica is used as the abrasive grains, the surface of the colloidal silica may be modified with a silane coupling agent or the like.

[0025] The surface of colloidal silica can be modified with a silane coupling agent by the following immobilization method. For example, the method described in "Sulfonic acid-functionalized silica through of thiol groups", Chem. Commun. 246-247 (2003) can be used. Specifically, a silane coupling agent having a thiol group, such as 3-mercaptopropyltrimethoxysilane, is coupled to colloidal silica, and then the thiol group is oxidized with hydrogen peroxide to obtain colloidal silica with sulfonic acid immobilized on the surface.

[0026] Alternatively, for example, it can be carried out by the method described in "Novel Silane Coupling Agents Containing a Photolabile 2-Nitrobenzyl Ester for Introduction of a Carboxy Group on the Surface of Silica Gel", Chemistry Letters, 3, 228-229 (2000). Specifically, a silane coupling agent containing a photolabile 2-nitrobenzyl ester is coupled to colloidal silica, and then the resulting mixture is irradiated with light to obtain colloidal silica having a carboxylic acid fixed on the surface.

[0027] The above is a colloidal silica having an anionic group (anion-modified colloidal silica), but a colloidal silica having a cationic group (cation-modified colloidal silica) may also be used. An example of a colloidal silica having a cationic group is colloidal silica having an amino group fixed on the surface. As a method for producing such colloidal silica having a cationic group, a method of fixing a silane coupling agent having an amino group, such as aminoethyltrimethoxysilane, aminopropyltrimethoxysilane, aminoethyltriethoxysilane, aminopropyltriethoxysilane, aminopropyldimethylethoxysilane, aminopropylmethyldiethoxysilane, or aminobutyltriethoxysilane, on the surface of colloidal silica, as described in JP-A-2005-162533, can be mentioned. This makes it possible to obtain colloidal silica having an amino group fixed on the surface.

[0028] The average primary particle diameter of the abrasive grains is preferably 5 nm or more, more preferably 10 nm or more, and even more preferably 15 nm or more. As the average primary particle diameter of the abrasive grains increases, the polishing rate of the object to be polished by the polishing composition increases. In addition, the average primary particle diameter of the abrasive grains is preferably 120 nm or less, more preferably 80 nm or less, and even more preferably 50 nm or less. As the average primary particle diameter of the abrasive grains decreases, it becomes easier to obtain a surface with fewer defects by polishing with the polishing composition. The average primary particle diameter of the abrasive grains can be calculated, for example, based on the specific surface area (SA) of the abrasive grains calculated by the BET method, assuming that the shape of the abrasive grains is a true sphere. In this specification, the average primary particle diameter of the abrasive grains is a value measured by the method described in the Examples.

[0029] The average secondary particle diameter of the abrasive grains is preferably 30 nm or more, more preferably 40 nm or more, and even more preferably 50 nm or more. As the average secondary particle diameter of the abrasive grains increases, the resistance during polishing decreases, and stable polishing becomes possible. In addition, the average secondary particle diameter of the abrasive grains is preferably 250 nm or less, more preferably 200 nm or less, even more preferably 150 nm or less, and particularly preferably 100 nm or less. As the average secondary particle diameter of the abrasive grains decreases, the surface area per unit mass of the abrasive grains increases, the contact frequency with the object to be polished increases, and the polishing speed increases. The average secondary particle diameter of the abrasive grains can be measured, for example, by a dynamic light scattering method represented by a laser diffraction scattering method. In this specification, the average secondary particle diameter of the abrasive grains is a value measured by the method described in the Examples.

[0030] The upper limit of the aspect ratio of the abrasive grain is not particularly limited, but is preferably less than 2.0, more preferably 1.8 or less, and even more preferably 1.6 or less. In such a range, defects on the surface of the object to be polished can be further reduced. The aspect ratio is the average value obtained by taking the smallest rectangle that circumscribes the image of the abrasive grain by a scanning electron microscope, and dividing the length of the long side of the rectangle by the length of the short side of the same rectangle, and can be obtained using general image analysis software. The lower limit of the aspect ratio of the abrasive grain in the polishing composition is not particularly limited, but is preferably 1.0 or more.

[0031] In the particle size distribution of abrasive grains obtained by laser diffraction scattering method, the lower limit of D90 / D10, which is the ratio of the particle diameter (D90) when the cumulative particle weight from the fine particle side reaches 90% of the total particle weight and the particle diameter (D10) when the cumulative particle weight from the fine particle side reaches 10% of the total particle weight of all particles, is not particularly limited, but is preferably 1.1 or more, more preferably 1.2 or more, and even more preferably 1.3 or more. In addition, in the particle size distribution of abrasive grains in a polishing composition obtained by laser diffraction scattering method, the upper limit of the ratio D90 / D10, which is the particle diameter (D90) when the cumulative particle weight from the fine particle side reaches 90% of the total particle weight and the particle diameter (D10) when the cumulative particle weight from the fine particle side reaches 10% of the total particle weight of all particles, is not particularly limited, but is preferably 2.04 or less. Within such a range, defects on the surface of the object to be polished can be further reduced.

[0032] The size of the abrasive grains (average primary particle size, average secondary particle size, aspect ratio, D90 / D10, etc.) can be appropriately controlled by selecting the manufacturing method of the abrasive grains, etc.

[0033] The content (concentration) of the abrasive grains in the polishing composition is not particularly limited, but is preferably 0.05% by mass or more, more preferably 0.1% by mass or more, and even more preferably 0.3% by mass or more, based on the total mass of the polishing composition. The upper limit of the content of the abrasive grains is preferably 20% by mass or less, more preferably 10% by mass or less, and even more preferably 5% by mass or less, based on the total mass of the polishing composition. That is, the content of silica is preferably 0.05% by mass or more and 20% by mass or less, more preferably 0.1% by mass or more and 10% by mass or less, and even more preferably 0.3% by mass or more and 5% by mass or less, based on the total mass of the polishing composition. Within such a range, the polishing speed of the object to be polished can be improved while suppressing costs. In addition, when the polishing composition contains two or more kinds of abrasive grains, the content of the abrasive grains refers to the total amount of these.

[0034] (Inorganic salts) The polishing composition of the present embodiment contains an inorganic salt. Such an inorganic salt increases the electrical conductivity of the polishing composition and compresses the electric double layer on the silicon germanium surface. Therefore, the action of the abrasive grains on the silicon germanium surface can be improved, and the polishing speed of silicon germanium can be improved.

[0035] The inorganic salt is not particularly limited, but examples thereof include salts of monovalent inorganic acids, salts of divalent inorganic acids, and salts of trivalent inorganic acids.

[0036] Examples of monovalent inorganic acids include hydrochloric acid, nitric acid, nitrous acid, etc. Examples of divalent inorganic acids include sulfuric acid, carbonic acid, sulfurous acid, thiosulfuric acid, phosphonic acid, etc. Examples of trivalent inorganic acids include phosphoric acid, phosphomolybdic acid, phosphotungstic acid, vanadic acid, etc.

[0037] Examples of the salts of these monovalent inorganic acids, divalent inorganic acids, and trivalent inorganic acids include lithium salts, sodium salts, potassium salts, calcium salts, magnesium salts, and ammonium salts.

[0038] More specific examples of inorganic salts include sodium nitrate, potassium nitrate, ammonium nitrate, magnesium nitrate, calcium nitrate, sodium nitrite, potassium nitrite, lithium carbonate, sodium carbonate, potassium carbonate, magnesium carbonate, calcium carbonate, lithium hydrogen carbonate, sodium hydrogen carbonate, potassium hydrogen carbonate, ammonium carbonate, sodium bicarbonate, sodium sulfate, potassium sulfate, ammonium sulfate, calcium sulfate, magnesium sulfate, sodium sulfite, potassium sulfite, calcium sulfite, magnesium sulfite, potassium thiosulfate, lithium sulfate, magnesium sulfate, sodium thiosulfate, sodium hydrogen sulfite, ammonium hydrogen sulfate, lithium hydrogen sulfate, sodium hydrogen sulfate, potassium hydrogen sulfate, trilithium phosphate, tripotassium phosphate, trisodium phosphate, triammonium phosphate, disodium hydrogen phosphate, dipotassium hydrogen phosphate, diammonium hydrogen phosphate, sodium dihydrogen phosphate, potassium dihydrogen phosphate, ammonium dihydrogen phosphate, etc. These inorganic salts can be used alone or in combination of two or more.

[0039] Among these, from the viewpoint of preventing metal contamination of the object to be polished, the inorganic salt is preferably at least one selected from the group consisting of ammonium nitrate, ammonium sulfate, ammonium hydrogen sulfate, triammonium phosphate, diammonium hydrogen phosphate, and ammonium dihydrogen phosphate, more preferably ammonium sulfate and triammonium phosphate, and even more preferably ammonium sulfate.

[0040] The content (concentration) of the inorganic salt in the polishing composition is not particularly limited, but is preferably 0.01% by mass or more, more preferably 0.02% by mass or more, and even more preferably 0.05% by mass or more, based on the total mass of the polishing composition. The upper limit of the content of the inorganic salt in the polishing composition used in the present invention is preferably 5% by mass or less, more preferably 3% by mass or less, and even more preferably 1% by mass or less, based on the total mass of the polishing composition. When the content of the inorganic salt is 0.01% by mass or more, the electric double layer of the silicon germanium film is sufficiently compressed, making it easier for the abrasive grains to contact the silicon germanium film, and the polishing speed of the silicon germanium film can be increased. When the content of the inorganic salt is 5% by mass or less, the electric conductivity can be suppressed from increasing, so that the electric double layer of the abrasive grains and the film other than silicon germanium (for example, silicon oxide film, silicon nitride film) is compressed, making it difficult for the abrasive grains to contact the film other than silicon germanium, and the increase in the polishing speed of the film other than silicon germanium can be suppressed. In addition, deterioration of storage stability due to an increase in electrical conductivity can be suppressed.

[0041] When the polishing composition contains two or more kinds of inorganic salts, the content of the inorganic salts refers to the total amount of these.

[0042] (Oxidizing agent) The polishing composition of the present embodiment contains an oxidizing agent. The oxidizing agent has the effect of oxidizing the surface of silicon germanium, and can further increase the polishing rate of silicon germanium with the polishing composition.

[0043] Examples of the oxidizing agent include hydrogen peroxide, sodium peroxide, barium peroxide, ozone water, silver (II) salts, iron (III) salts, permanganic acid, chromic acid, dichromate, peroxodisulfuric acid, peroxolinic acid, peroxosulfuric acid, peroxoboric acid, performic acid, peracetic acid, perbenzoic acid, perphthalic acid, hypochlorous acid, hypobromous acid, hypoiodous acid, chloric acid, chlorous acid, perchloric acid, bromic acid, iodic acid, periodic acid, persulfuric acid, dichloroisocyanuric acid, and salts thereof. These oxidizing agents can be used alone or in combination of two or more.

[0044] Among these, the oxidizing agent is preferably one that does not contain a halogen atom, and hydrogen peroxide is more preferable.

[0045] The lower limit of the content (concentration) of the oxidizing agent in the polishing composition is preferably 0.001% by mass or more, and more preferably 0.01% by mass or more. By setting the lower limit in this way, the polishing speed of silicon germanium can be further improved. In addition, the upper limit of the content of the oxidizing agent in the polishing composition is preferably 5% by mass or less, and more preferably 3% by mass or less. By setting the upper limit in this way, it is possible to reduce the material cost of the polishing composition, and also to reduce the burden of treating the polishing composition after use in polishing, that is, the waste liquid treatment. In addition, it is also possible to reduce the risk of excessive oxidation of the surface of the object to be polished by the oxidizing agent.

[0046] (polishing accelerator) The polishing composition of the present embodiment may further contain a polishing accelerator.

[0047] The polishing accelerator according to the present invention is adsorbed on the surface of the Ge oxide film and has a function of partially modifying the Ge oxide film. The modified Ge oxide film is highly processable and has a high polishing rate, but is unlikely to dissolve and is considered to suppress etching.

[0048] Such a polishing accelerator preferably has an acid group, such as a carboxy group, a phosphoric acid group, a phosphonic acid group, a sulfuric acid group, or a sulfonic acid group.

[0049] Specific examples of the polishing accelerator include, for example, ethylenediaminetetraacetic acid, nitrilotriacetic acid, hydroxyethylethylenediaminetriacetic acid, diethylenetriaminepentaacetic acid, triethylenetetraminehexaacetic acid, N-(2-hydroxyethyl)ethylenediamine-N,N',N'-triacetic acid, glycol ether diaminetetraacetic acid, 1,3-propanediamine-N,N,N',N'-tetraacetic acid, 1,3-diamino-2-propanol-N,N,N',N'-tetraacetic acid, N-(2-hydroxyethyl)iminodiacetic acid, methyl acid phosphate, ethyl acid phosphate, ethyl glycol acid phosphate, isopropyl acid phosphate, phytic acid, 1-hydroxyethylidene-1,1-diphosphonic acid, aminotri(methylenephosphonic acid), diethylenetriaminepenta(methylenephosphonic acid), aminopoly(methylenephosphonic acid), 2-aminoethylphosphonic acid, nitrile, Rilotri(methylenephosphonic acid), N,N,N',N'-Ethylenediaminetetrakis(methylenephosphonic acid), Diethylenetriaminepenta(methylenephosphonic acid), Ethane-1,1-diphosphonic acid, Ethanehydroxy-1,1,2-triphosphonic acid, Ethane-1-hydroxy-1,1,2-triphosphonic acid, Ethane-1,2-dicarboxy-1,2-diphosphonic acid, Methanehydro Examples of such an acid include xyphosphonic acid, 2-phosphonobutane-1,2-dicarboxylic acid, 2-phosphonobutane-1,2,4-tricarboxylic acid, α-methylphosphonosuccinic acid, N,N-di(2-hydroxyethyl)glycine, aspartic acid, glutamic acid, dicarboxymethylglutamic acid, (S,S)-ethylenediamine-N,N'-disuccinic acid, 2,3-dihydroxybenzoic acid, iminodiacetic acid, etidronic acid, mugineic acid, and salts thereof.

[0050] The polishing accelerator can be used alone or in combination of two or more kinds. The polishing accelerator can be a synthetic product or a commercially available product. Examples of commercially available polishing accelerators include Chelesto PH-430, Chelesto PH-540, Chelesto GA, Chelesto EDDS-4H, and Chelesto HA (all manufactured by Chelesto Co., Ltd.).

[0051] Among these polishing accelerators, from the viewpoint of being able to independently improve the processing speed of silicon germanium without changing the processing speed of other film types such as silicon oxide films and silicon nitride films, at least one selected from the group consisting of N-(2-hydroxyethyl)ethylenediamine-N,N',N'-triacetic acid, N,N,N',N'-ethylenediaminetetrakis(methylenephosphonic acid), 2-phosphonobutane-1,2,4-tricarboxylic acid, N,N-di(2-hydroxyethyl)glycine, aspartic acid, and (S,S)-ethylenediamine-N,N'-disuccinic acid is preferred, more preferably selected from N,N,N',N'-ethylenediaminetetrakis(methylenephosphonic acid) and 2-phosphonobutane-1,2,4-tricarboxylic acid, and even more preferably N,N,N',N'-ethylenediaminetetrakis(methylenephosphonic acid).

[0052] The content (concentration) of the polishing accelerator in the polishing composition is not particularly limited, but is preferably 0.01 mass% or more, more preferably 0.05 mass% or more, and even more preferably 0.08 mass% or more, based on the total mass of the polishing composition. The upper limit of the content of the polishing accelerator in the polishing composition is preferably 5 mass% or less, more preferably 3 mass% or less, and even more preferably 1 mass% or less, based on the total mass of the polishing composition. Within such a range, the polishing speed of silicon germanium can be further improved.

[0053] When the polishing composition contains two or more kinds of polishing accelerators, the content of the polishing accelerators refers to the total amount thereof.

[0054] (pH adjuster) The polishing composition of this embodiment can contain a pH adjuster to adjust the pH to 6.0 or higher.

[0055] The pH adjuster is not particularly limited as long as it is a compound having a pH adjusting function, and known compounds can be used. Examples of the pH adjuster include acids and alkalis.

[0056] The acid may be either an inorganic acid or an organic acid. The inorganic acid is not particularly limited, but examples thereof include sulfuric acid, nitric acid, boric acid, carbonic acid, hypophosphorous acid, phosphorous acid, and phosphoric acid. The organic acid is not particularly limited, but examples thereof include carboxylic acids such as formic acid, acetic acid, propionic acid, butyric acid, valeric acid, 2-methylbutyric acid, n-hexanoic acid, 3,3-dimethylbutyric acid, 2-ethylbutyric acid, 4-methylpentanoic acid, n-heptanoic acid, 2-methylhexanoic acid, n-octanoic acid, 2-ethylhexanoic acid, benzoic acid, glycolic acid, salicylic acid, glyceric acid, oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, maleic acid, phthalic acid, malic acid, tartaric acid, citric acid, and lactic acid, as well as methanesulfonic acid, ethanesulfonic acid, and isethionic acid.

[0057] The alkali is not particularly limited, but examples thereof include alkali metal hydroxides such as potassium hydroxide, ammonia, quaternary ammonium salts such as tetramethylammonium and tetraethylammonium, amines such as ethylenediamine and piperazine, etc. Among these, ammonia is more preferable.

[0058] The pH adjusters may be used alone or in combination of two or more kinds.

[0059] The content of the pH adjuster is not particularly limited, and may be appropriately adjusted so that the polishing composition has a desired pH.

[0060] (dispersion medium) The polishing composition of this embodiment may contain a dispersion medium for dispersing each component. Examples of the dispersion medium include water; alcohols such as methanol, ethanol, and ethylene glycol; ketones such as acetone, and mixtures thereof. Of these, water is preferred as the dispersion medium. That is, according to a more preferred embodiment of the present invention, the dispersion medium contains water. According to a further preferred embodiment of the present invention, the dispersion medium is substantially composed of water. Note that the above "substantially" means that a dispersion medium other than water may be included as long as the objective effect of the present invention can be achieved, and more specifically, the dispersion medium is preferably composed of 90% by mass or more and 100% by mass or less of water and 0% by mass or more and 10% by mass or less of a dispersion medium other than water, and more preferably composed of 99% by mass or more and 100% by mass or less of water and 0% by mass or more and 1% by mass or less of a dispersion medium other than water. Most preferably, the dispersion medium is water.

[0061] From the viewpoint of not inhibiting the action of the components contained in the polishing composition, it is preferable for the dispersion medium to be water that contains as few impurities as possible. Specifically, pure water or ultrapure water from which impurity ions have been removed with an ion exchange resin and then foreign matter has been removed through a filter, or distilled water is more preferable.

[0062] (Other Ingredients) The polishing composition of this embodiment may further contain other components such as complexing agent, preservative, and antifungal agent as necessary. The content of other components may be appropriately set according to the purpose of adding them. Hereinafter, the other components, i.e., preservative and antifungal agent, will be described.

[0063] Examples of the preservatives and antifungal agents include isothiazoline preservatives such as 2-methyl-4-isothiazolin-3-one, 5-chloro-2-methyl-4-isothiazolin-3-one, 1,2-benzoisothiazolin-3-one, 2-n-octyl-4-isothiazolin-3-one, paraoxybenzoic acid esters, orthophenylphenol, phenoxyethanol, etc. These preservatives and antifungal agents may be used alone or in combination of two or more kinds.

[0064] (pH of polishing composition) The pH of the polishing composition of this embodiment is not particularly limited as long as it is 6.0 or more, and can be appropriately adjusted according to the combination of abrasive grains, inorganic salt, and oxidizing agent used.The lower limit of pH is preferably 7.0 or more, preferably 8.0 or more, and more preferably 9.0 or more.The upper limit of pH is, for example, 13.0 or less, preferably 12.0 or less, and more preferably 11.0 or less.If the pH is less than 6.0, the etching reaction of silicon germanium becomes poor, and the polishing rate is significantly reduced.If the pH is more than 13, the stability of the polishing composition cannot be maintained.

[0065] The pH of the polishing composition can be measured with a pH meter (manufactured by Horiba, Ltd., model number: LAQUA).

[0066] (Method of manufacturing the polishing composition) The method for producing the polishing composition of this embodiment is not particularly limited, and can be obtained, for example, by stirring and mixing abrasive grains, inorganic salt, oxidizing agent, and other additives as necessary in a dispersion medium (e.g., water). The details of each component are as described above. Therefore, the present invention provides a method for producing a polishing composition, which includes the step of mixing abrasive grains, inorganic salt, and oxidizing agent.

[0067] The temperature at which the components are mixed is not particularly limited, but is preferably 10° C. to 40° C. Heating may be performed to increase the dissolution rate. The mixing time is also not particularly limited as long as the components can be mixed uniformly.

[0068] (Application) The polishing composition of the present embodiment is preferably used for polishing an object to be polished that contains silicon germanium. The germanium content in the object to be polished, that is, silicon germanium, is preferably 10 mass % or more.

[0069] The object to be polished according to the present embodiment may contain other silicon-containing materials as long as it contains silicon germanium. Examples of silicon-containing materials include elemental silicon and silicon compounds. Examples of elemental silicon include single crystal silicon, polycrystalline silicon (polysilicon, Poly-Si), and amorphous silicon. Examples of silicon compounds include silicon nitride (SiN), silicon oxide (SiO 2 ), silicon carbide, etc. Silicon-containing materials also include low-dielectric-constant materials with a relative dielectric constant of 3 or less.

[0070] Examples of films containing silicon oxide include TEOS (Tetraethyl Orthosilicate) type silicon oxide films (hereinafter simply referred to as "TEOS films") produced using tetraethyl orthosilicate as a precursor, HDP (High Density Plasma) films, USG (Undoped Silicate Glass) films, PSG (Phosphorus Silicate Glass) films, BPSG (Boron-Phospho Silicate Glass) films, and RTO (Rapid Thermal Oxidation) films.

[0071] [Polishing method and semiconductor substrate manufacturing method] One aspect of the present invention is a polishing method including a step of polishing an object to be polished with the polishing composition.

[0072] Another aspect of the present invention is a method for producing a semiconductor substrate, comprising the step of polishing a semiconductor substrate by the polishing method described above.

[0073] In the polishing method of this embodiment, the polishing apparatus used can be a general polishing apparatus equipped with a holder for holding a substrate or the like having an object to be polished, a motor capable of changing the rotation speed, and the like, and having a polishing platen onto which a polishing pad (polishing cloth) can be attached.

[0074] The polishing pad may be made of any material, including general nonwoven fabric, polyurethane, porous fluororesin, etc. It is preferable that the polishing pad has grooves formed thereon to allow the polishing liquid to accumulate.

[0075] Regarding the polishing conditions, for example, the rotation speed of the polishing platen was 10 rpm (0.17 s -1 ) or more 500rpm(8.3s -1 ) or less. The pressure (polishing pressure) applied to the substrate having the object to be polished is preferably 0.5 psi (3.4 kPa) or more and 10 psi (68.9 kPa) or less. The method of supplying the polishing composition to the polishing pad is not particularly limited, and for example, a method of continuously supplying the composition using a pump or the like is used. There is no limit to the amount of supply, but it is preferable that the surface of the polishing pad is always covered with the polishing composition of the present invention.

[0076] After polishing, the substrate is washed with running water, and water droplets adhering to the substrate are removed by a spin dryer or the like, followed by drying to obtain a substrate having a metal-containing layer.

[0077] The polishing composition used in the polishing method of this embodiment may be a one-liquid type or a multi-liquid type such as a two-liquid type. The polishing composition used in the polishing method of this embodiment may be prepared by diluting the stock solution of the polishing composition, for example, 10 times or more, with a diluent such as water.

[0078] The polishing rate when silicon germanium is polished by the polishing method of this embodiment is preferably 280 Å / min or more, more preferably 300 Å / min or more, and even more preferably 400 Å / min or more. Furthermore, the etching amount of silicon germanium when silicon germanium is polished by the polishing method of this embodiment is preferably 80 Å or less, and more preferably 60 Å or less. The polishing rate and etching amount can be measured by the method described in the Examples.

[0079] The polishing method of the present embodiment can be applied to a polishing object containing silicon germanium and other materials, and in this case, the effect that the ratio of the polishing rate of silicon germanium to the polishing rate of other materials is sufficiently high (i.e., the selectivity is sufficiently high) can be obtained. For example, when the other material is silicon nitride, the ratio of the polishing rate of silicon germanium to the polishing rate of silicon nitride ([polishing rate of silicon germanium] / [polishing rate of silicon nitride]) is preferably 15 or more, more preferably 20 or more, and even more preferably 25 or more. In addition, when the other material is silicon oxide, the ratio of the polishing rate of silicon germanium to the polishing rate of silicon oxide ([polishing rate of silicon germanium] / [polishing rate of silicon oxide]) is preferably 10 or more, more preferably 13 or more. EXAMPLES

[0080] The present invention will be described in more detail using the following examples and comparative examples. However, the technical scope of the present invention is not limited to the following examples. Unless otherwise specified, "%" and "parts" mean "% by mass" and "parts by mass", respectively. In the following examples, unless otherwise specified, the operations were performed under the conditions of room temperature (20 to 25°C) / relative humidity 40 to 50% RH.

[0081] Example 1 The polishing composition contains colloidal silica (average primary particle size: 29 nm, average secondary particle size: 61 nm, silanol group density: 1.50 / nm 2 The polishing composition was prepared by adding 0.5% by mass of ammonium sulfate (aspect ratio 1.55), 0.1% by mass of ammonium sulfate as an inorganic salt, and 0.16% by mass of hydrogen peroxide as an oxidizing agent. These components were mixed by stirring in pure water (mixing temperature: about 25°C, mixing time: about 10 minutes). The pH was adjusted to 10.4 using ammonia as a pH adjuster.

[0082] Example 2 A polishing composition was prepared in the same manner as in Example 1, except that ammonium sulfate was changed to triammonium phosphate.

[0083] Example 3 A polishing composition was prepared in the same manner as in Example 1, except that the content of colloidal silica was changed to 1.0 mass %.

[0084] Example 4 A polishing composition was prepared in the same manner as in Example 1, except that the content of ammonium sulfate was changed to 0.2 mass %.

[0085] Example 5 A polishing composition was prepared in the same manner as in Example 1, except that the pH was adjusted to 9.2.

[0086] Example 6 A polishing composition was prepared in the same manner as in Example 1, except that the content of hydrogen peroxide was changed to 0.40 mass %.

[0087] Example 7 The polishing composition contains colloidal silica (average primary particle size: 29 nm, average secondary particle size: 61 nm, silanol group density: 1.50 / nm 2 The following components were added to the polishing composition: 0.5% by mass of ammonium sulfate as an inorganic salt, 0.1% by mass of hydrogen peroxide as an oxidizing agent, and 0.1% by mass of N,N,N',N'-ethylenediaminetetrakis(methylenephosphonic acid) (EDTMP) as a polishing accelerator. These components were mixed by stirring in pure water (mixing temperature: about 25°C, mixing time: about 10 minutes). The pH was adjusted to 10.4 using ammonia as a pH adjuster to prepare a polishing composition.

[0088] Example 8 The polishing composition contains colloidal silica (average primary particle size: 29 nm, average secondary particle size: 61 nm, silanol group density: 1.50 / nm 2The following components were added to the polishing composition: 0.5% by mass of ammonium phosphate trihydrate (aspect ratio 1.55), 0.1% by mass of triammonium phosphate as an inorganic salt, 0.16% by mass of hydrogen peroxide as an oxidizing agent, and 0.1% by mass of 2-phosphonobutane-1,2,4-tricarboxylic acid (PBTC) as a polishing accelerator. These components were mixed by stirring in pure water (mixing temperature: about 25°C, mixing time: about 10 minutes). The pH was adjusted to 9.2 using ammonia as a pH adjuster to prepare a polishing composition.

[0089] Comparative Example 1 The polishing composition contains colloidal silica (average primary particle size 34 nm, average secondary particle size 70 nm, silanol group density 5.71 / nm 2 0.5% by mass of stearate, aspect ratio 1.19) and 0.16% by mass of hydrogen peroxide as an oxidizing agent were added. These components were mixed by stirring in pure water (mixing temperature: about 25°C, mixing time: about 10 minutes). The pH was adjusted to 9.2 using ammonia as a pH adjuster to prepare a polishing composition.

[0090] Comparative Example 2 The polishing composition contains colloidal silica (average primary particle size 34 nm, average secondary particle size 70 nm, silanol group density 5.71 / nm 2 The polishing composition was prepared by adding 0.5% by mass of ammonium sulfate (aspect ratio 1.19), 0.1% by mass of ammonium sulfate as an inorganic salt, and 0.16% by mass of hydrogen peroxide as an oxidizing agent. These components were mixed by stirring in pure water (mixing temperature: about 25°C, mixing time: about 10 minutes). The pH was adjusted to 9.2 using ammonia as a pH adjuster.

[0091] Comparative Example 3 A polishing composition was prepared in the same manner as in Comparative Example 2, except that the pH was adjusted to 10.4.

[0092] Comparative Example 4 The polishing composition contains colloidal silica (average primary particle size 34 nm, average secondary particle size 70 nm, silanol group density 5.71 / nm2 The polishing composition was prepared by adding 0.5% by mass of stearate, aspect ratio 1.19), 0.1% by mass of potassium sulfate as an inorganic salt, and 0.16% by mass of hydrogen peroxide as an oxidizing agent. These components were mixed by stirring in pure water (mixing temperature: about 25°C, mixing time: about 10 minutes). The pH was adjusted to 10.4 using potassium hydroxide as a pH adjuster.

[0093] Comparative Example 5 The polishing composition contains colloidal silica (average primary particle size: 29 nm, average secondary particle size: 61 nm, silanol group density: 1.50 / nm 2 0.5% by mass of 1,2-dichloroethane (aspect ratio 1.55) and 0.16% by mass of hydrogen peroxide as an oxidizing agent were added. These components were mixed by stirring in pure water (mixing temperature: about 25°C, mixing time: about 10 minutes). The pH was adjusted to 10.4 using ammonia as a pH adjuster to prepare a polishing composition.

[0094] Comparative Example 6 A polishing composition was prepared in the same manner as in Comparative Example 5, except that the content of colloidal silica was changed to 4.0 mass %.

[0095] [Measurement of pH of polishing composition] The pH of the polishing composition (liquid temperature: 25° C.) was confirmed with a pH meter (manufactured by Horiba, Ltd., model number: LAQUA).

[0096] [Measurement of average primary particle size and average secondary particle size] The average primary particle size of the abrasive grains was calculated from the specific surface area of ​​the abrasive grains measured by the BET method using "Flow Sorb II 2300" manufactured by Micromeritics, and the density of the abrasive grains.

[0097] The average secondary particle size of the abrasive grains was measured using a dynamic light scattering particle size / particle size distribution analyzer UPA-UTI151 manufactured by Nikkiso Co., Ltd.

[0098] [Silanol group density measurement] The number of silanol groups per unit surface area of ​​the abrasive grains (silanol group density) was calculated by the Sears method using neutralization titration described in Analytical Chemistry, vol. 28, No. 12, 1956, 1982-1983 by GW Sears. The number of silanol groups was calculated using the following formula.

[0099]

number

[0100] The composition of the polishing composition prepared above is shown in Table 1.

[0101] [Table 1]

[0102] [Polishing speed] The following wafers were prepared as polishing objects: Silicon germanium (SiGe) wafer: A silicon wafer (300 mm, blanket wafer, manufactured by Advanced Material Technology Co., Ltd.) with a 1500 Å thick silicon germanium film (Si:Ge = 50:50 mass ratio) formed on the surface. Silicon oxide (TEOS) wafer: A silicon wafer with a 10,000 Å thick silicon oxide film formed on its surface (300 mm, blanket wafer, manufactured by Advantec Co., Ltd.) Silicon nitride (SiN) wafer: A silicon wafer with a 3500 Å thick silicon nitride film formed on its surface (300 mm, blanket wafer, manufactured by Advantec Corporation).

[0103] The polishing rates of silicon germanium wafers, silicon oxide wafers, and silicon nitride wafers were determined when the wafers were polished for a certain period of time under the polishing conditions shown in Table 2 below using the polishing compositions of Examples 1 to 8 and Comparative Examples 1 to 6. The silicon germanium wafers, silicon oxide wafers, and silicon nitride wafers were prepared by cutting 300 mm substrates into 60 mm x 60 mm coupons.

[0104] [Table 2]

[0105] The polishing speed (polishing rate) was calculated according to the following formula.

[0106]

number

[0107] The thickness of the silicon oxide and silicon nitride films was measured using an optical interference film thickness measuring device, Lambda Ace VM-2030, manufactured by SCREEN Semiconductor Solutions Co., Ltd., and was evaluated by dividing the difference in film thickness before and after polishing by the polishing time.

[0108] The thickness of the silicon germanium film was measured using a scanning X-ray fluorescence analyzer ZSX Primus 400 manufactured by Rigaku Corporation, and was evaluated by dividing the difference in film thickness before and after polishing by the polishing time.

[0109] The selectivity ratio of the polishing rate was determined by calculating the polishing rate of silicon germanium / polishing rate of silicon oxide and the polishing rate of silicon germanium / polishing rate of silicon nitride, respectively.

[0110] [Etching amount] A silicon germanium wafer (Si:Ge=50:50 mass ratio) measuring 30 mm x 30 mm was immersed in the polishing composition rotated at 300 rpm using a stirrer at 43°C for 1 hour, and the amount of dissolution (amount of etching) was calculated based on the difference in film thickness before and after immersion.

[0111] The evaluation results are shown in Table 3 below.

[0112] [Table 3]

[0113] As is clear from Table 3 above, the polishing compositions of the Examples have a sufficiently high polishing rate for silicon germanium compared to the polishing compositions of the Comparative Examples, and the ratio (selectivity) of the polishing rate for silicon germanium to the polishing rate for silicon oxide or silicon nitride is also sufficiently high.

Claims

1. The polishing agent includes an abrasive grain, an inorganic salt, and an oxidizing agent, The number of silanol groups per unit surface area of ​​the abrasive grain is 0 / nm 2 More than 2.0 pieces / nm 2 is as follows: The pH is 6.0 or more, The abrasive grains are colloidal silica; the inorganic salt is at least one selected from the group consisting of ammonium sulfate, ammonium hydrogen sulfate, triammonium phosphate, diammonium hydrogen phosphate, and ammonium dihydrogen phosphate; the oxidizing agent is at least one selected from the group consisting of hydrogen peroxide, sodium peroxide, barium peroxide, ozone water, permanganic acid, chromic acid, dichromate, peroxodisulfuric acid, peroxolinic acid, peroxosulfuric acid, peroxoboric acid, performic acid, peracetic acid, perbenzoic acid, perphthalic acid, persulfuric acid, and salts thereof, and when the oxidizing agent is hydrogen peroxide, the content of the hydrogen peroxide is 0.16% by mass or more and 5% by mass or less; A polishing composition for use in polishing an object containing silicon germanium.

2. The polishing composition according to claim 1 , wherein the inorganic salt is ammonium sulfate.

3. The polishing composition according to claim 1 or 2, wherein the oxidizing agent is hydrogen peroxide.

4. The polishing composition according to any one of claims 1 to 3, further comprising a polishing accelerator.

5. The polishing composition according to claim 4, wherein the polishing accelerator is at least one selected from the group consisting of N-(2-hydroxyethyl)ethylenediamine-N,N',N'-triacetic acid, N,N,N',N'-ethylenediaminetetrakis(methylenephosphonic acid), 2-phosphonobutane-1,2,4-tricarboxylic acid, N,N-di(2-hydroxyethyl)glycine, aspartic acid, and (S,S)-ethylenediamine-N,N'-disuccinic acid.

6. 6. A polishing method comprising a step of polishing an object containing silicon germanium with the polishing composition according to claim 1.

7. A method for producing a semiconductor substrate, comprising the step of polishing a semiconductor substrate containing silicon germanium by the polishing method according to claim 6.

Citation Information

Patent Citations

  • Polishing solution for metal and chemical mechanical polishing method

    JP2008288537A

  • Aqueous dispersion for chemo-mechanical polishing and manufacturing method thereof, and chemo-mechanical polishing method

    JP2010034497A

  • Aqueous dispersion for chemical mechanical polishing and method of manufacturing the same, and chemical mechanical polishing method

    JP2010041027A

  • Polishing composition

    JP2015067752A

  • Polishing composition and producing method thereof and polishing method

    JP2016069535A